Tingkat sikap Dan pengetahuan Tim Medis Tentang Keperawatan Paliatif Di Rumah Sakit Umum Daerah Lagita - Doloksaribu, Kevin Putraim Manuel; Br perangin-angin, Mori Agustina (Coping: Community of Publishing in Nursing, 2020)
Palliative care is an approach to improve the quality of life of patients in the face of life-threatening diseases by alleviating suffering from pain and providing physical, psychosocial, and spiritual support from the time of diagnosis to the end of the patient's life. Of the 40 billion cases in the world, only 24% receive palliative care, which is the lack of knowledge of the medical team on near-death care and one indicator of the need for a positive attitude in caring for palliative patients. The aim of this study was to determine the level of knowledge and attitudes of the medical team about palliative care in Lagita Regional General Hospital. Data were collected by descriptive quantitative correlation and sampling was carried out by means of convinence with sampling 68 medical teams but 7 data was incomplete so that 61 medical teams from Lagita Regional General Hospital were included. Data was collected from October-November 2020. Measuring the level of knowledge The Palliative Care Quiz for Nursing (PCQN) questionnaire was used and attitudes measure used the Frommelt's Attitude Toward Care of the Dying (FATCOD) scale questionnaire. The conclusion was that there was no close relationship between the medical team's attitudes and knowledge of near-death care p value> 0.05. Knowledge is in the sufficient category, while the attitude is in the negative category, the results of this test are carried out with rho and training is needed to increase the knowledge of the medical team and the length of work to increase the positive attitude of the medical team towards dying patients at the Lagita Regional General Hospital.